Pengaruh Debt to Equity Ratio, Current Ratio, dan Total Asset Turnover terhadap Return on Equity pada Perusahaan Consumer Goods Industry - Indah Astry Wahyuni Sagala; Cathrine J Pane; Evrina Yolanda; Ningsih Firda Yanti; Maya Sabirina Panggabean (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Debts to Equty, Current Ratio, and Total Turnover of Assets to Return On Equity in the Consumer Goods Industry Company that were found on the Indonesia Stock Exchange for the period 2013-2018. This study uses a sample of 19 Consumer Goods Industry companies that were found on the Indonesia Stock Exchange in the period 2013-2018. This research is quantitative research. The data used are secondary data obtained from the site www.Idx.co.id. The sampling method is Purposive Sampling. Data analysis method used is multiple linear testing. The results showed that the Debt to Equity was insignificant to Return on Capital, the current ratio was calculated partially and significantly to Return on Capital and Total Asset Turnover was not partially related and not significant to Return on Capital. Meanwhile, all independent variables in this study support Return on Equity.